BEARING WEAR ANALYSIS IN MULTI-BEARING SPINDLE SYSTEM - ZHANG Yu; FU XueYan; LI Shuang; LI SongHua (Jixie qiangdu)
In order to clarify the effects of different working condition parameters and quantify their influence degree on bearing wear in the spindle system, the bearing wear in the spindle system supported by multi-bearing was carried out. Firstly, the calculation method of wear coefficient considering the lubrication state is introduced, and the wear depth model of the angular contact ball bearing is deduced. Second, the wear depth of the inner and outer raceways of the bearing is calculated based on the motion parameters and contact parameters of the bearing rolling elements obtained from the system model. The influences of spindle speed, bearing angular misalignment caused by mounting error, external loads and bearing surface roughness on bearing wear are discussed. The results show that the spindle speed has a significant impact on bearing wear, and the change of spindle speed leads to a great difference of bearing wear law. Without bearing angular misalignment, the sum of the wear depth of the inner and outer raceways of each bearing in the spindle system is the smallest. The change of external loads has little effect on bearing wear, but the increase in surface roughness can significantly increase the wear depth of the bearing.